2023
DOI: 10.1186/s12906-023-03844-w
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to 8-methyl nonanoic acid, a degradation by-product of dihydrocapsaicin, in 3T3-L1 adipocytes

Abstract: Background Capsaicinoids, such as dihydrocapsaicin (DHC), exert the health-promoting effects of chili peppers on energy metabolism. The metabolic responses to capsaicinoids are primarily mediated through transient receptor potential cation channel subfamily V member 1 (TRPV1). However, the varying contributions of their metabolites to beneficial health outcomes remain unclear. 8-methyl nonanoic acid (8-MNA), a methyl-branched medium chain fatty acid (MCFA), is an in vivo degradation by-product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Hydrolysis of capsaicin and dihydrocapsaicin, which is biologically relevant, produces 8-methyl-6-trans-nonenoic and 8-methylnonanoic acids, respectively. These MCFAs have been shown to possess beneficial biological properties of their own 37) . Thus, we undertook this work, to investigate the possibility to obtain these fatty acids from enzymatic hydrolysis of purified capsaicinoids and to incorporate them into a triglyc-Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis of capsaicin and dihydrocapsaicin, which is biologically relevant, produces 8-methyl-6-trans-nonenoic and 8-methylnonanoic acids, respectively. These MCFAs have been shown to possess beneficial biological properties of their own 37) . Thus, we undertook this work, to investigate the possibility to obtain these fatty acids from enzymatic hydrolysis of purified capsaicinoids and to incorporate them into a triglyc-Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, their metabolism leads to the formation of ketone bodies, which are thought of as having beneficial biological properties, for example as potential energy source for the central nervous system 34,36) . A recent publication studying in detail the effects of 8-methylnonanoic acid on 3T3-L1 pre adipocytes has shown the ability of this fatty acid to inhibit the differentiation of these cells into adipocytes 37) . Interesting-ly, our initial results have shown that the mixture of fatty acids obtained from the enzymatic hydrolysis of purified capsaicinoids exhibits similar properties.…”
mentioning
confidence: 99%